‘Opt-out’ referrals after identifying pregnant smokers using exhaled air carbon monoxide: impact on engagement with smoking cessation support - Campbell, Katarzyna; Cooper, Sue; Fahy, Samantha; Bowker, Katharine; Leonardi-Bee, Jo; McEwen, Andy; Whitemore, Rachel; Coleman, Tim (BMJ Publishing Group, 2017)
Background. In the UK, free smoking cessation support is available to pregnant women; only a minority access this. ‘Opt-out’ referrals to stop smoking services (SSS) are recommended by UK guidelines. These involve identifying pregnant smokers using exhaled carbon monoxide (CO) and referring them for support unless they object.